Patterns of land cover and land use change within the two major metropolitan areas of Ghana. Issue 2 (25th January 2020) - Toure, Sory I.; Stow, Douglas A.; Clarke, Keith; Weeks, John
Abstract: Sub-Saharan Africa is the region of the world experiencing the highest rates of urbanization and population growth. However, the expansion of cities in sub-Saharan Africa is following a different trajectory than cities in the rest of the world, especially in Europe and North America. Indeed, urbanization on the African subcontinent has not been preceded by economic development and industrialization. The objective of this study is to improve our understanding of the process of urbanization in sub-Saharan Africa by comparing and contrasting two major cities of Ghana, Accra and Kumasi. We combined remote sensing methods and spatial metrics to compare the growth, built-up density, land use composition, and fragmentation of Accra and Kumasi between 2000 and 2010. Results show that Accra and Kumasi grew at an annual rate of 4.5% and 6% respectively. Residential land use constituted the major addition in both cities. Accra, the capital city of Ghana, added the most non-residential built-up land. Moreover, growth in both cities was compact, with new built-up land use occurring adjacent to existing urban land at the beginning of the study period in 2000. Finally, the urban-rural interface located within a 2 km buffer beyond the urban core experienced the greatest amount of fragmentation between 2000 and 2010 for both cities.